The countercyclical capital buffer and international bank lending: Evidence from Canada - David Chen; Christian Friedrich (Bank of Canada, 2021)
We examine the impact of the recently introduced Basel III countercyclical capital buffer (CCyB) on foreign lending activities of Canadian banks. Using panel data for the six largest Canadian banks and their foreign activities in up to 94 countries, we explore the variation in CCyB rates across countries to overcome the identification challenge associated with limited time-series evidence on the use of the CCyB in individual jurisdictions. Our main sample focuses on the period from 2013Q2 to 2019Q3, when CCyB rates experienced a prolonged tightening cycle. We show that in response to a 1-percentage-pointtightening announcement in a foreign CCyB, the growth rate of cross-border lending between Canadian banks' head offices and borrowers in CCyB-implementing countries decreases by between 12 and 17 percentage points. Most importantly, due to the CCyB's unique reciprocity rule, which also subjects foreign banks to domestic regulation, the direction of this effect differs from that of other forms of foreign capital regulation that have been previously examined in the literature. When investigating the underlying transmission channels of a CCyB change, we find that, in particular, large banks are more able than small banks to shield their cross-border lending against the impact of foreign CCyB changes. Finally, when focusing on the loosening cycle in CCyB rates that emerged in early 2020, we show that our findings on the differential effects for large and small banks also carry over to the COVID-19 episode-a time when various jurisdictions rapidly released their CCyBs to stabilize their banks' lending activities.
Keywords: E32; F21; F32; G21; G28; 330; Credit risk management; Financial institutions; Financial stability; Financial systemregulation and policies; International topics